STRATEGIES APPLIED BY ENGLISH TEACHERS TO OVERCOME THE PROBLEMS IN IMPLEMENTING 2013 CURRICULUM AT SMAN 1 LINTAU BUO - Lena Sastri (English Language Teaching and Research, 2018)
SMA N 1 Lintau Buo has applied 2013 curriculum almost 5 years, but English teachers who teach there still face some problems in implementing it. This study aims to investigate English teachers’ problems and their strategies to overcome the problems. This study adopted descriptive qualitative design, and the data were collected through interview of three English teachers at SMAN 1 Lintau Buo. Finding showed that there were some problems faced in implementing 2013 curriculum. They got difficulties in using many types of authentic assessments and the rubrics, the shortage of English duration (2 credit hours) that made students were not ensure to improve their English competences at school, and difference materials between 2013 curriculum and 2006 curriculum (materials for UN especially for twelfth grade). To solve these problems, the teachers had different strategies. They used some of authentic assessments (affective and psychomotor), calculated and managed effective weeks, made lesson plans, prota and prosem properly in order to all materials can be taught to the students, and completed 2013 curriculum materials in first semester and focused on UN materials in second semester.Keywords: implementing 2013 curriculum, problems, strategies